Two pairs of farnesyl phenolic enantiomers as natural nitric oxide inhibitors from Ganoderma sinense. Issue 14 (15th July 2016) - Wang, Meng; Wang, Fei; Xu, Feng; Ding, Li-Qin; Zhang, Qian; Li, Hui-Xiang; Zhao, Feng; Wang, Li-Qing; Zhu, Li-Han; Chen, Li-Xia; Qiu, Feng
Graphical abstract: Abstract: Four new farnesyl phenolic compounds, ganosinensols A–D (1 –4 ) were isolated from the 95% EtOH extract of the fruiting bodies of Ganoderma sinense . Two pairs of enantiomers, 1 /2, and3 /4 were isolated by HPLC using a Daicel Chiralpak IE column. Their structures were elucidated from extensive spectroscopic analyses and comparison with literature data. The absolute configurations of1 –4 were assigned by ECD spectra. All of these isolated compounds showed potent inhibitory activity against LPS-induced nitric oxide production in RAW 264.7 macrophages, with IC50 values from 1.15 to 2.26 μM.